A Novel Relay Station Deployment Scheme for beyond 4G Multi-hop Network. (2016) - Jishnu, C.K.; Babu, K. Vinoth; Arthi, M.; Arulmozhivarman, P.
Abstract: In Long Term Evolution-Advanced (LTE-A) and Worldwide interoperability for microwave access (WiMAX) systems, the coverage area, signal strength and transmission quality are affected by white Gaussian noise, shadowing, wireless interference etc. This effect can be decreased by using more number of evolved NodeBs (eNB), but problem is that eNBs are expensive and it will increase network cost. Relay Stations (RS) are less expensive than eNBs, hence we go for RS deployment instead of eNBs. Thus this paper proposes a cost effective deployment of RSs using dynamic cost based deployment of RS (DCDR) approach. This approach first analyse the impact parameters and then finds the dynamic weighting and network cost for different deployment combination. Simulation result shows that DCDR approach gives a cost effective solution for the deployment of RSs.